Peran Guru Dalam Menerapkan Pembelajaran PPKn Sebagai Pendidikan Politik Bagi Pemilih Pemula - Esty Rahmayanti (FKIP, Universitas Palangka Raya, 2023)
This research aims to describe the role and obstacles faced by teachers in implementing PPKn learning as political education for beginner voters at public high schools in Yogyakarta City. This research is descriptive research with a qualitative approach. The data analysis used includes data collection, data reduction, presentation and conclusions. The results of this research are as follows. 1) The role of teachers as instructors is to provide understanding and direction regarding the form of active participation of novice voters as citizens in casting their right to vote correctly. 2) The role of teachers as educators is to instill political values ​​and try to influence the political orientation of novice voters so that they have political awareness, political concern and political participation. 3) The role of the teacher as a guide is to guide and direct students to have knowledge, skills and independence in carrying out national and state life. 2) The obstacles faced by teachers are as follows. (a) There are still students who are less interested in politics, they are less enthusiastic and pay less attention to the teacher's explanations, so that the instillation of political values ​​is less than optimal. (b) There are still students who have a negative view of politics and think that politics only prioritizes the interests of certain groups. (c) The voting behavior of novice voter students still depends very much on their parents' choices, not on their political awareness.